The Predictive Impact of Cultural Values and Ideology on Employer-Employees Relations in Contemporary Nigeria - Adigun, Abel. O. (Archives of Business Research, 2016)
This study investigated the predictive impact of cultural values and ideology on employer-employees relations in contemporary Nigeria. Using a descriptive survey research design, simple random sampling technique was used to select four hundred employer-employees from ten manufacturing organisations in Ibadan, Nigeria. A self-constructed questionnaire (0.84) was used to collect relevant data for the study. Two research questions were answered and two hypotheses tested at 0.05 level of significance. Data were analysed using Multiple Regression and Pearson Product Moment Correlation statistical tool. There was significant relationship between the independent variables and the dependent variable. Also, the independent variables accounted for 45.5% of the total variance on the predictive impact of cultural values and ideology on employer-employees relations in contemporary Nigeria. In order of magnitude, of the contribution: ideology has more influence on employer-employees relations (? =0.373, t = 2.246, P < 0.05) followed by cultural values (? = 0. 156, t = 1.668, P < 0.05). Therefore, Management should ensure appropriate work orientation is given to workers so that they will be conscious of their organizations cultural values and ideological philosophy as to support the growth of the organization.